Qualidade de cultivares de grãos de arroz submetidos à secagem e armazenagem em silo-secador-aerador - Moraes, Rosana Santos de (2022)
The quality of rice grains can be influenced by several factors, including during the postharvest stages, such as grain drying. In addition, the characteristics of the cultivar influence the quality of rice grains. Thus, the objective of this study was to evaluate the changes in the physical, physicochemical and morphological properties of different cultivars of rice grains submitted to drying in silos-dryers-aerators. The quality of three rice grain cultivars (IRGA 424, BRS Pampeira and Guri INTA) was evaluated in two positions in the grain column (upper and lower layer) submitted to drying and storage in three silo-dryer-aerator, equipped with a system of thermometry and aeration. The rice grains were processed to obtain polished rice and the samples were submitted to the evaluation of whole grain and broken grain yield, physical classification, physicochemical and morphological quality. To evaluate the results, analysis of variance was performed, comparing the means by Tukey's test at 5% probability of error and using methods of near-infrared spectroscopy, X-ray diffraction analysis, scanning electron microscopy techniques and statistical analysis multivariate. As the drying time increased, the water contents of the grains entered hygroscopic equilibrium with 12% (w.b.) in the lower layer and 14% (w.b.) in the upper layer of the grain mass, the largest difference being observed for cultivar IRGA 424. The height of the grain mass increased the drying time of the grains in the upper layers of the silo-dryer-aerator. The permanence for a long period of the grain mass with high water contents provided an increase in the temperature of the grain mass, influencing the quality of the polished rice. Drying of paddy rice in a single thick layer at low temperatures preserved the physical, physicochemical and morphological quality of rice in the lower layers until the period of two months of drying. The mass of rice grains of the cultivars Guri INTA and BRS Pampeira presented greater uniformity of drying and final quality in the processed rice.